2014
DOI: 10.4049/jimmunol.1401037
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Malaria Exposure Are Associated with Changes in the B Cell Pool and in Plasma Eotaxin Levels

Abstract: Pregnancy triggers immunological changes aimed to tolerate the fetus, but its impact on B lymphocytes is poorly understood. In addition, exposure to the Plasmodium parasite is associated with altered distribution of peripheral memory B cell (MBC) subsets. To study the combined impact of high malaria exposure and pregnancy in B cell subpopulations, we analyzed PBMCs from pregnant and nonpregnant individuals from a malaria-nonendemic country (Spain) and from a high malaria-endemic country (Papua New Guinea). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 59 publications
6
55
0
1
Order By: Relevance
“…Eotaxin concentrations were decreased in pregnancy (27,30) and correlated very well with Treg frequencies, but the latter did not express the main eotaxin receptor CCR3, which suggests that this chemokine is not involved in the redistribution of Tregs during pregnancy. We were surprised to find a relatively strong negative correlation between IL-12 concentration and T H 1 cell frequency and between TGF-b concentration and Treg frequency, because these cytokines are known to trigger differentiation of those cellular subsets.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Eotaxin concentrations were decreased in pregnancy (27,30) and correlated very well with Treg frequencies, but the latter did not express the main eotaxin receptor CCR3, which suggests that this chemokine is not involved in the redistribution of Tregs during pregnancy. We were surprised to find a relatively strong negative correlation between IL-12 concentration and T H 1 cell frequency and between TGF-b concentration and Treg frequency, because these cytokines are known to trigger differentiation of those cellular subsets.…”
Section: Discussionmentioning
confidence: 88%
“…5A), and a negative correlation with TGF-b (q = 0.009). Eotaxin levels are decreased during pregnancy and in individuals exposed to malaria (27,30). We have previously demonstrated that memory B cells express eotaxin receptor CCR3 (27) and activated murine Tregs express also this receptor (31).…”
Section: Correlation Between T Cells and Plasma Cytokine And Chemokinmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that higher proportions of IgD - atypical memory B cells are observed in P . vivax exposed pregnant and non-pregnant women compared to non-exposed individuals [57]. An controlled P .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whether atypical MBCs differentiate from classical MBCs or whether they originate from different precursors is still controversial (Muellenbeck et al 2013;Portugal et al 2015). An expanded atypical MBC pool is found in people who are chronically exposed to or infected with malaria, and a higher frequency of atypical MBCs is found in patients who reported at least one previous malaria episode compared to no previous exposure (Weiss et al 2009(Weiss et al , 2011Illingworth et al 2013;Ampomah et al 2014;Requena et al 2014). These atypical MBCs upregulate inhibitory receptors such as Fc receptor ligand 3 (FcRL3) and FcRL5, and show diminished BCR signaling, proliferation, and cytokine production (Portugal et al 2015;Sullivan et al 2015).…”
Section: Impaired Humoral Immunitymentioning
confidence: 99%